2003
DOI: 10.1016/s0896-6273(03)00331-3
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic Orexin Neurons Regulate Arousal According to Energy Balance in Mice

Abstract: Mammals respond to reduced food availability by becoming more wakeful and active, yet the central pathways regulating arousal and instinctual motor programs (such as food seeking) according to homeostatic need are not well understood. We demonstrate that hypothalamic orexin neurons monitor indicators of energy balance and mediate adaptive augmentation of arousal in response to fasting. Activity of isolated orexin neurons is inhibited by glucose and leptin and stimulated by ghrelin. Orexin expression of normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

41
770
4
9

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 842 publications
(824 citation statements)
references
References 64 publications
41
770
4
9
Order By: Relevance
“…Orexin neurons are known to discharge during active waking [41], and the excitability is inhibited by glucose [1,4,6]. In addition, changes in blood glucose levels negatively correlate with expression of the gene encoding prepro-orexin in the mouse hypothalamus [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Orexin neurons are known to discharge during active waking [41], and the excitability is inhibited by glucose [1,4,6]. In addition, changes in blood glucose levels negatively correlate with expression of the gene encoding prepro-orexin in the mouse hypothalamus [11].…”
Section: Discussionmentioning
confidence: 99%
“…This may explain why the incidence of type 2 diabetes increases in orexin-deficient human narcolepsy without severe obesity. Furthermore, the expression of the gene for preproorexin is downregulated in diabetic ob/ob and db/db mice [47], and the downregulation is shown to be due to hyperglycaemia in these animals [4]. These suggest that diabetic hyperglycaemia reduces the expression of the gene for prepro-orexin in the hypothalamus, and thereby further worsens the insulin resistance.…”
Section: Irmentioning
confidence: 97%
See 1 more Smart Citation
“…However, by feeding HFD for 9 weeks, blood glucose level, but not triglycerides level is shown to be increased [22]. It has been reported that most orexin neurons are glucose sensitive, while the activity of isolated orexin neurons is hyperpolarized and their firing frequency is decreased by a high glucose level [23]. Thus, it is suggested that the hyperglycemic state induced by HFD cause the decrease of prepro-orexin mRNA level directly or indirectly in the hypothalamus in our feeding conditions.…”
Section: Discussionmentioning
confidence: 97%
“…Food seeking and food intake require vigilant states which require high energy expenditure. Recent evidence suggests that orexin neurons are capable of sensing indicators of energy balance and are activated under negative energy balance, such as decreased extracellular glucose level, reduced leptin level (an anorexigenic protein hormone secreted by adipocytes), and increased ghrelin level (a stomach-derived orexigenic peptide) (Yamanaka et al, 2003;Burdakov et al, 2005). Recently, non-essential amino acids were also reported to activate orexin neurons, which may potentially benefit an animal under prolonged starvation where a rise in extracellular amino acid levels occurs as proteins are broken down for fuel (Karnani et al, 2011).…”
Section: Integrative Physiology Of Orexin Systemmentioning
confidence: 99%